Розробка оптимального складу таблеток із діючою речовиною калій 2-((4-аміно-5-(морфолінометил)-4Н-1,2,4-тріазол-3-іл)тіо) ацетатом. Повідомлення 1. Вивчення впливу допоміжних речовин на насипну густину, насипну густину після усадки, текучість і кут природного укосу порошкових мас - Щербина, Роман Олександрович; Хромильова, Ольга Володимирівна; Німенко, Ганна Романівна; Саліонов, Володимир Олександрович; Shcherbyna, R. O.; Khromylоva, O. V.; Nimenko, H. R.; Salionov, V. O. (Запорізький державний медико-фармацевтичний університет, 2024)
Мета роботи – вивчення впливу допоміжних речовин на фармако-технологічні показники таблеток із діючою речовиною калій 2-((4-аміно-5-(морфолінометил)-4Н-1,2,4-тріазол-3-іл)тіо)ацетатом, отриманих методом прямого пресування. Матеріали і методи. Діюча речовина – калій 2-((4-аміно-5-(морфолінометил)-4Н-1,2,4-тріазол-3-іл)тіо)ацетат, допоміжні речовини (на основі мікрокристалічної целюлози, гранульованих цукрів, ковзні, змащувальні речовини). Перевірили порошкові суміші на насипну густину, насипну густину після ущільнення, текучість і кут природного укосу. Пресували таблетки методом прямого пресування. Досліджено вплив допоміжних речовин на процес пресування. Результати. У результаті досліджень встановили, що порошкова маса 2-((4-аміно-5-(морфолінометил)-4Н-1,2,4-тріазол-3-іл)тіо) ацетату калію та допоміжних речовин характеризувалася хорошими фармако-технологічними показниками – насипною густиною і насипною густиною після ущільнення, текучістю і кутом природного укосу. Далі у процесі таблетування підтверджено, що порошкова маса має задовільні властивості. Майже у всіх серіях експерименту процес пресування таблеток перебігав нормально, матриця рівномірно заповнена, але сила виштовхування таблеток із матриці різна. The aim of the work was to study the effect of excipients on the pharmaco-technological parameters of tablets with the active ingredient potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio)acetate obtained by the method direct pressing. Materials and methods. Active substance – potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio)acetate, auxiliary substances (excipients based on microcrystalline cellulose, auxiliary substances based on granulated sugars, lubricants, lubricants). The powder mixtures were checked for bulk density, bulk density after compaction, flowability and angle of natural slope. The tablets were pressed by the direct pressing method. The effect of auxiliary substances on the pressing process was studied. Results. The conducted studies show that the powder mass of potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio)acetate and auxiliary substances was characterized by good pharmaco-technological indicators – bulk density and bulk density after compaction, fluidity and angle of natural slope. Further, during the tableting process, it was confirmed that the powder mass has satisfactory properties. In almost all series of experiments, the process of pressing the tablets took place without difficulties, the matrix was evenly filled, but the force of pushing the tablets out of the matrix was different. Conclusions. The study involving 16 excipients, including fillers, disintegrants, and lubricants to develop the composition and technology was conducted of a new tablet medicine containing potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazole-3-yl)thio)acetate. This comprehensive examination enabled us to identify the optimal auxiliary substances that fulfill all the pharmaco-technological requirements stipulated by the State Pharmacopoeia of Ukraine for tablet formulations.
Development of the optimal composition of tablets with the active substance potassium 2-((4-amino-5-(morpholinomethyl)- 4H-1,2,4-triazol-3-yl)thio)acetate. Message 1. Study of the effect of auxiliary substances on bulk density, bulk density after shrinkage, fluidity and angle of natural slope of powder masses
Щербина Р. О. - ORCID ID: 0000-0002-9742-0284; Хромильова О. В. - ORCID ID: 0000-0002-5274-9676; Німенко Г. Р. - ORCID ID: 0000-0002-6486-5113; Саліонов В. О. - ORCID ID: 0000-0003-4914-0509.
Keywords: 1,2,4-тріазол; фармако-технологічні показники; таблетована лікарська форма; пряме пресування; 1,2,4-triazole; pharmaco-technological indicators; tablet; dosage form; direct pressing